Psychoactive Prescription Practices for Serious Mental and Neurological Illness in Ghana: Data from the Mental Health and Poverty Project (MHaPP). Issue 4 (1st October 2016) - Canavan, Maureen; Sipsma, Heather; Jack, Helen; Ohene, Sammy; Rohrbaugh, Robert; Bradley, Elizabeth; Ofori-Atta, Angela; ,
Abstract: Mental disorders are disabling and economically costly health conditions. Given limited resources, mental health systems in low- and middle-income countries (LMICs) tend to focus on patients with the most severe conditions, for whom treatment usually relies on use of psychoactive medications; however, inconsistent patterns of use can be ineffective, wasteful, and potentially harmful. Therefore, a greater understanding of prescription practices and medication availability in LMIC is needed. We estimated associations between prescription practices and hospitals and medication availability for patients diagnosed with schizophrenia or delusional disorders (n = 7, 296) and patients diagnosed with epilepsy (n = 1, 807), the two most common mental and neurological disorders seen at Ghana's psychiatric hospitals. Among patients with a primary diagnosis of schizophrenia or delusional disorders, 43% were prescribed an anti-psychotic or combination of anti-psychotics and anti-cholinergics. Among patients with a diagnosis of epilepsy, 67% were prescribed only anti-convulsants. More than 83% of patients with schizophrenia or delusional disorders had prescribed medication available, while the prescribed medications were available for 61% of patients with epilepsy. Availability varied by prescription type. The importance of understanding the medication treatment process for these mental disorders is crucial. Although most patients are prescribed medications consistent with their diagnoses, the use of multiple classes of medications and nonavailability of prescribed medications are issues that challenge the quality of care. Efforts such as Mental Health and Poverty Project (MHaPP), which establish reliable data collection and monitoring of patient diagnosis and treatment, are critical for transforming services for people with serious mental illness in resource-constrained settings.